Analysis of Evidence of Witchcraft Crimes Based on the New Indonesian Criminal Code - Jeremia Hutagalung; Setiadi, Edi; Yanto, Oksidelfa (Sinergi International Journal of Law, 2025)
The pluralistic life of beliefs about spiritual matters in Indonesia is very thick and sensitive, especially the occurrence of criminal acts that are beyond common sense or cannot be proven by scientific criminal investigations, namely criminal acts of black magic perpetrators or victims of black magic which result in violations of human rights (HAM). Belief in religion which is a source of morality and spirituality which is considered as part of a tradition that has never been abandoned by Indonesian society with situations and conditions of high spiritual values makes Indonesian people's belief in God and spirits that live around humans or those that smell mystical or black magic not uncommon in every region with their respective cultural characteristics, for example human rights violations in Banyumas Regency, namely the massacre allegedly carried out by black magic perpetrators with 250 victims. With this belief, it is not uncommon for people in some areas to have or even have the ability to see supernatural things or study black magic, for their own interests. So the question arises as a problem identification, namely 1. How are efforts to prove the crime of black magic according to Law Number 1 of 2023 concerning the Criminal Code? 2. How can the elements of black magic be called a criminal act based on Law Number 1 of 2023 concerning the Criminal Code? The research method used by the author is the normative legal approach method. The normative legal approach is a legal research conducted by examining library materials or secondary data as a basis for research by tracing laws and regulations and literature related to the problems studied by the author.